2018
DOI: 10.1186/s12944-018-0834-1
|View full text |Cite
|
Sign up to set email alerts
|

Free fatty acid can induce cardiac dysfunction and alter insulin signaling pathways in the heart

Abstract: BackgroundInsulin resistance has been independently related to heart failure. However, the specific mechanisms of high FFA levels in the pathophysiology of heart failure in insulin-resistant states are remain largely unclear. This study investigated whether elevated circulating free fatty acids (FFA) levels result in impaired cardiac structure and function in vivo via insulin-related signaling pathways in myocardium.MethodsMale Wistar rats were randomly divided into the intralipid group (20% intralipid plus he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 34 publications
0
21
0
1
Order By: Relevance
“…Its typical manifestation is the increase of TG and free fatty acid (FFA) [44][45][46][47] . Increased FFA is an independent pathogenic factor for insulin resistance and can possibly increase the risk for cardiovascular diseases 48,49 . Therefore, the improvement of dyslipidemia is beneficial for not only regulating insulin sensitivity but also controlling the occurrence and progression of diabetic complications 50,51 .…”
Section: Discussionmentioning
confidence: 99%
“…Its typical manifestation is the increase of TG and free fatty acid (FFA) [44][45][46][47] . Increased FFA is an independent pathogenic factor for insulin resistance and can possibly increase the risk for cardiovascular diseases 48,49 . Therefore, the improvement of dyslipidemia is beneficial for not only regulating insulin sensitivity but also controlling the occurrence and progression of diabetic complications 50,51 .…”
Section: Discussionmentioning
confidence: 99%
“…Free fatty acids (FFAs) are intermediate products of lipid mobilization that result principally from lipolysis and the breakdown of triglycerides (TGs) (Stich and Berlan 2004). Previous studies have reported that FFA levels are associated with unfavorable functional outcomes in stroke and cardiovascular disease and may play a role in the process of disease progression (Choi et al 2014;Sun et al 2015;Xiong et al 2015;Duan et al 2017;Han et al 2018). In clinical work, we found that in some cancer patients, the FFA level was elevated even when TGs and total cholesterol (TCHO) were normal, and a high FFA level may be the only abnormality in biochemical tests.…”
Section: Introductionmentioning
confidence: 99%
“…Supporting this idea, our data suggest that even relatively short high fat diet interferes with PI3K-Aktpathway restricting the final steps of growth and functional maturation before adulthood. Also other diet compositions leading to obesity and FA accumulation could produce the same outcome, as PI3K inhibition and excess FA intake are strongly linked (Fang et al, 2008;Han et al, 2018;Zhang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%